Late mesoproterozoic to early paleozoic history of metamorphic basement from the southeastern Chiapas Massif Complex, Mexico, and implications for the evolution of NW Gondwana - Weber, Bodo; Cisneros de León, Alejandro (Lithos, 2018)
Abstract: In this paper, U-Pb zircon geochronology, Lu-Hf and Sm-Nd isotope systematics, geochemistry and geothermobarometry of metaigneous basement rocks exposed in the southeastern Chiapas Massif Complex are presented. Geologic mapping of the newly defined “El Triunfo Complex” located at the southeastern edge of the Chiapas Massif reveals (1) partial melting of a metamorphic basement mainly constituted by mafic metaigneous rocks (Candelaria unit), (2) an Ediacaran metasedimentary sequence (Jocote unit), and (3) occurrence of massif-type anorthosite. All these units are intruded by undeformed Ordovician plutonic rocks of the Motozintla suite. Pressure and temperature estimates using Ca-amphiboles, plagioclase and phengite revealed prograde metamorphism that reached peak conditions at ~ 650 °C and ~ 6 kbar, sufficient for partial melting under water saturated conditions. Relict rutile in titanite and clinopyroxene in amphibolite further indicate a previous metamorphic event at higher P-T conditions. U-Pb zircon ages from felsic orthogneiss boudins hosted in deformed amphibolite and migmatite yield crystallization ages of ~ 1.0 Ga, indicating that dry granitic protoliths represent remnants of Rodinia-type basement. Additionally, a mid-Tonian (~ 920 Ma) metamorphic overprint is suggested by recrystallized zircon from a banded gneiss. Zircon from folded amphibolite samples yield mainly Ordovician ages ranging from ~ 457 to ~ 444 Ma that are indistinguishable from the age of the undeformed Motozintla plutonic suite. Similar ages between igneous- and metamorphic- zircon suggest a coeval formation during a high-grade metamorphic event, in which textural discrepancies are explained in terms of differing zircon formation mechanisms such as sub-solidus recrystallization and precipitation from anatectic melts. In addition, some amphibolite samples contain inherited zircon yielding Stenian-Tonian ages around 1.0 Ga. Lu-Hf and Sm-Nd isotopes and geochemical data indicate that the protoliths of the amphibolite have E-MORB characteristics and were derived from a depleted mantle source younger than the Rodinia-type basement. Inasmuch as similar amphibolites also occur in the Ediacaran metasedimentary rocks as dykes or lenses, Late Neoproterozoic magmatism in a rift setting is suggested. Hence, the geologic record of the El Triunfo Complex includes evidences for Rodinia assemblage, Tonian circum-Rodinia subduction, and breakup during the Late Neoproterozoic. Metamorphism, and partial melting are interpreted in terms of a convergent margin setting during the Ordovician. The results place the southern Chiapas Massif along with Oaxaquia and similar Northern Andes terranes on the NW margin of Gondwana interpreted as the extension of the Famatinian orogen that evolved during the closure of the Iapetus Ocean.
Gesehen am 27.06.2019
Available online: 13 December 2017